2019
DOI: 10.4028/www.scientific.net/msf.971.106
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influencing Factors of Noise Reduction Performance of Pervious Concrete

Abstract: In this experiment, four kinds of pervious concrete with different porosity (10%, 15%, 20%, 25%), four kinds of paste coating thickness (0.3mm, 0.5mm, 0.7mm, 0.9mm) and four kinds of thickness (30mm, 40mm, 50mm, 60mm) were prepared and their sound absorption coefficients under different frequency bands were tested. The results show that with the increase of target porosity, the thickness of paste coating and the thickness of pervious concrete, the sound absorption coefficient of pervious concrete increases fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Porous concrete material, as an important part of sponge city, is paid more and more attention by researchers and engineers, and gradually becomes a research hotspot [1][2][3]. Duo to the porous structure, porous concrete has many advantages in solving urban problems such as urban hot islands, transportation-related noise, urban waterlogging and drop of groundwater [4][5][6][7]. However, porous concrete has many connected pores, which results in its mechanical properties and durability not as good as ordinary concrete [8].…”
Section: Introductionmentioning
confidence: 99%
“…Porous concrete material, as an important part of sponge city, is paid more and more attention by researchers and engineers, and gradually becomes a research hotspot [1][2][3]. Duo to the porous structure, porous concrete has many advantages in solving urban problems such as urban hot islands, transportation-related noise, urban waterlogging and drop of groundwater [4][5][6][7]. However, porous concrete has many connected pores, which results in its mechanical properties and durability not as good as ordinary concrete [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cai Jiangning [3] et al studied the effect of carbon fiber and steel fiber blending on the mechanical properties of concrete, and the results showed that the best enhancement of compressive strength and tensile strength with the same volume of blended fiber, and the toughness of each group of concrete was significantly improved. Wang Jinlong [4] et al studied the effect of imitation steel fiber admixture and other factors on the mechanical properties of concrete, and the results showed that when the PPTF admixture is 3~4 kg/m 3 , the admixture of PPTF increases the bridging action and bonding surface between the aggregates, which limits the deformation of concrete and synergizes the force with the aggregates.…”
Section: Introductionmentioning
confidence: 99%